Curriculum Reform in Indonesia: English Education Toward The Global Competitiveness - Pajarwati, Dian; Mardiah, Hikmatul; Harahap, Ronitama Parsaulian; Siagian, Rusliani Octavia; Ihsan, Muhammad Taufik (Education and Talent Development Center Indonesia (ETDC Indonesia), 2021)
The aims of this paper is to provide an understanding to everyone that it is necessary to know the development of curriculum reform in Indonesia, especially in the case of using English in the current era of globalization. This can be seen from the history of curriculum development in Indonesia, until the importance of using English language education in global competition. This writing is made in the form of a study of documents and literatures whose understanding of knowledge is used as an analysis. In view of this, Indonesian can learn from other countries that have succeeded in reforming and developing English curriculum while taking into account the uniqueness of its own context.